Pins and needles - Talbot, John, 1948- (New York : Dial Books for Young Readers, 1992)
Feeling a tingly "pins-and-needles" sensation in his trunk from having slept on it all night, Jean Pierre the elephant tries different remedies to cure himself.
Publisher's Weekly
School Library Journal
Kirkus Reviews
5.1
K-3
Keywords: Elephants -- Fiction; Elephants -- Fiction